2018
DOI: 10.20944/preprints201801.0236.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Problematic Use of the Internet and Smartphones in University Students: 2006–2017

Abstract: 1) Background: It has been more than a decade since the concern about addictive use of the Internet and mobile phones was first expressed and its possible inclusion into the lists of mental disorders has been a popular topic of discussion recently, thus it seems to be a fitting moment to investigate the networks are considered responsible for this increase, and females are the ones perceived to be more affected than males. The degree to which participants agree with the statement "I am addicted to the Internet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…For them, a gadget is a compelling tool, a device which encompasses the whole of entertainment. It is not only a communication tool but it also increases their sense of autonomy, identity and even their credibility (Carbonell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For them, a gadget is a compelling tool, a device which encompasses the whole of entertainment. It is not only a communication tool but it also increases their sense of autonomy, identity and even their credibility (Carbonell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of frequency, the level of gadget addiction among Gen Z shows 3 respondents are normal gadget users while 313 respondents are addicted to gadgets. Studies conducted by Salehan and Negahban (2013), Zaremohzzabieh et al (2014), Teong & Ang (2016) and Carbonell et al (2018) found the use of gadgets at normal level may provide positive benefits, but the use of gadget at extreme and critical level is capable of disrupting the daily life of gadget users resulting in the decline of mental health, lack of focus in learning and affect socialization and academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre las variables sociodemográficas de control, se encontró un efecto significativo del sexo, pues el hecho de ser mujer se muestra como un predictor del uso problemático del smartphone, lo que coincide con diversos trabajos previos (Arnavut et al, 2018;Veissière & Stendel, 2018). Investigaciones anteriores han hallado que las mujeres hacen un uso fundamentalmente social del teléfono móvil, y dedican más tiempo a las aplicaciones relacionadas con la mensajería instantánea y las redes sociales (Carbonell et al, 2018); mientras que en los hombres los patrones de uso son más diversos (De-Sola et al, 2016). Tabla 3.…”
Section: Discussionunclassified